Public health nurses’ experiences of ethical responsibility: A meta-ethnography - Clancy, Anne; Hovden, Julia Thuve; Andersen, Runa Anneli; Laholt, Hilde (Nursing ethics, 2024)
Public health nursing is grounded in public health ideologies and fundamental nursing values. Researchers have argued that ethical responsibility from the perspective of the nurse is an understudied phenomenon. This meta-ethnography provides in-depth knowledge of how public health nurses (PHNs) experience ethical responsibility when working to prevent injury and disease, and promote health and well-being in children, young people and their families. There are reciprocal findings across the 10 included studies. The findings reveal that these nurses often feel alone, have worries and uncertainties and are afraid of doing wrong. They describe unclear boundaries in their work, creating a heightened sense of responsibility. PHNs fight lonely battles. Yet they show courage and commitment and are ready to stand up and fight for children and families who do not receive adequate care. A line of argument is developed and the metaphorical phrase Chivalrous knights in moral armour is used to express the authors’ overall interpretations of the findings. Reflection on the findings shows how the different dimensions of ethical responsibility are interconnected. The nurses’ ethical sensitivity enables them to feel compassion for others and they show indignation when vulnerable others are not treated with dignity and respect. Indignation and compassion are interrelated, and when human life and dignity are threatened, the ethical demand to respond emerges. Indignation is a precursor to moral courage, and the nurses’ moral sensitivity and respect for their clients emboldens them to stand up for vulnerable others. The findings also illustrate the paradoxical nature of freedom. Freedom of choice due to unclear boundaries heightens the nurses' sense of responsibility. This research is an important step in theory development and has implications for further research, education and practice.